Hubungan Pola Makanan Berserat dan Air Putih terhadap Kejadian Konstipasi di Sdit Darussalam Palembang - Lela Aini; Shinta Maharani; Lenny Astuti (Malahayati Nursing Journal, 2022)
ABSTRACT Constipation is a health problem in the form of not being able to pass hard and dry feces less than three times a week (Risma Hanuraswati, 2017). The pattern of bowel movements is influenced by several factors such as water intake, activity level, and fiber intake from the food you eat every day. Particular attention should be paid to consumption patterns that tend to emphasize practical benefits. Water supports metabolic processes in the body by converting food into energy. Our bodies can absorb 1.52 liters of water every day to support the body's own metabolism. This study aims to clarify the relationship between fiber diet and water on the development of constipation at SDIT Darussalam Palembang.   This type of survey is a quantitative survey with a descriptive analytical survey design using a cross-sectional approach. Based on the results of the study using paired t-test, the results of the systolic statistical test showed a value of 0.001. Since 0.05, we can conclude the relationship between food and water behavior in the development of constipation. Knowledge of the relationship between a high-fiber diet and normal water on the incidence of constipation at SDIT Darussalam Palembang, p-value = 0.001 Keywords: Constipation, Fiber Food, Water  ABSTRAK Konstipasi merupakan masalah kesehatan berupa tidak dapat mengeluarkan feses yang keras dan kering kurang dari tiga kali seminggu (Risma Hanuraswati, 2017). Pola buang air besar dipengaruhi oleh beberapa faktor seperti asupan air, tingkat aktivitas, dan asupan serat setiap orang. Air mendukung proses metabolisme dalam tubuh dengan mengubah makanan menjadi energi. Tubuh kita dapat menyerap 1,52 liter air setiap hari untuk mendukung metabolisme tubuh sendiri. Penelitian ini bertujuan untuk mengetahui hubungan pola makan berserat dan air putih terhadap perkembangan konstipasi di SDIT Darussalam Palembang. Jenis survei ini adalah survei kuantitatif dengan desain survei deskriptif analitis dengan menggunakan pendekatan cross-sectional. Berdasarkan hasil penelitian menggunakan uji t berpasangan, hasil uji statistik sistolik menunjukkan nilai 0,001. Karena α0,05, kita dapat menyimpulkan hubungan antara perilaku makanan dan air dalam perkembangan sembelit. Pengetahuan hubungan antara diet tinggi serat dan air putih normal terhadap kejadian konstipasi di SDIT Darussalam Palembang, p-value = 0,001 Kata Kunci: Konstipasi, Makanan, Beserat, Air Putih